Dampak Orientasi Pasar dan Inovasi terhadap Kinerja Pemasaran UMKM MMTC Kuliner Kota Medan - Sari, Aida Malan; Ardilla, Irna; Wahyundari, Sri Putri; Zainarti, Zainarti (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study analyzes the effect of market orientation and innovation on the marketing performance of culinary MMTC UMKM in Medan City. The problem formulation is to identify the effect of each independent variable on the dependent variable. The population used for this study were culinary MSMEs in the MMTC of Medan City. The data collection method uses interviews with several MMTC MSME actors in Medan City. The results of this study indicate that (1) market orientation has a significant influence on the marketing performance of culinary SMEs. (2) Innovation has a significant effect on marketing performance in culinary SMEs. This research has limitations in the number of variables, it is hoped that future research can pay attention to other factors so that it can increase the accuracy of research results in the context of improving marketing performance. The researcher suggests that MSME actors pay attention to other factors that can affect marketing performance.